PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN PADA CAFÉ TONG SUSU PEKANBARU (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at Café Tong Susu Pekanbaru located on Jalan Jend. Sudirman No.79, North Tengkerang, Kec. Bukit Raya, Pekanbaru City, Riau. The purpose of this study was to determine the effect of service quality and store atmosphere on consumer satisfaction at Café Tong Susu Pekanbaru partially and simultaneously. In this research, the method used is descriptive quantitative analysis with SPSS program. The population in this study is all consumers who made purchases at Café Tong Susu Pekanbaru in the last year, 2020 as many as2.272 people. Where the sample in this study were all consumers of Café Tong Susu Pekanbaru as many as 96 respondents. Data collection techniques through questionnaires, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale.From the data analysis which includes validity test, reliability test, multiple linear analysis, determination analysis and significance test with t test test (partial), and F test (simultaneous). The results of this study indicate that the results of testing the first t test hypothesis, service quality on customer satisfaction, namely t count (11,891)> t table (1,98552) meaning that service quality has a significant effect on consumer satisfaction. Second, store atmosphere on consumer satisfaction is t count (10,700) > t table (1,98552) meaning that store atmosphere has a significant effect on consumer satisfaction. The results of the F test of service quality and store atmosphere have a significant effect on customer satisfaction, namely count F count (104,314) > Ftable (3.09). This means that advertising and store atmosphere simultaneously have a significant effect on customer satisfaction at Café Tong Susu PekanbaruKeywords: Service Quality, Store Atmosphere, Consumer Satisfaction